2004
DOI: 10.1093/humrep/deh385
|View full text |Cite
|
Sign up to set email alerts
|

Early cleavage is a valuable addition to existing embryo selection parameters: a study using single embryo transfers

Abstract: BACKGROUND: To reduce the twin pregnancy rate, elective single embryo transfer (eSET) is increasingly implemented. Improvement of the results obtained with eSET can be achieved by better selection of the most viable embryo. This study investigated the predictive value of early cleavage (EC) as an additional parameter for selecting the embryo with the highest implantation potential by using data from SET's. METHODS: Data from 165 SET's were retrospectively evaluated. Cleavage to the 2-cell stage was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
3
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(86 citation statements)
references
References 33 publications
5
63
3
15
Order By: Relevance
“…Among of these criteria, morphologic features have been used extensively in selecting good-quality embryos. However, selection for transfer should not be based on cell number and morphology solely on the day of transfer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among of these criteria, morphologic features have been used extensively in selecting good-quality embryos. However, selection for transfer should not be based on cell number and morphology solely on the day of transfer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed that human embryos that cleaved earlier to the 2-cell stage exhibited a higher rate of blastocyst formation [15,16] compared with late cleaving embryos, and that transfer of the early cleaving embryos led to significantly higher implantation and pregnancy rates Fig. 3 Comparison of pregnancy rates between the early and late cleaved human embryos.…”
Section: Discussionmentioning
confidence: 98%
“…However, this quality control approach needs improvement with implantation rates of good quality embryos limited to 30-40 % per embryo transfer (ET) [7]. Indeed, based on the standard morphological assessment, ET with early cleavage-stage embryos has a better chance of achieving pregnancy than ET with blastocysts [8,9]. On the other hand, embryos at the blastocyst stage are less likely to be aneuploid, and reported implantation rates are higher when blastocysts have been transferred [10].…”
Section: Introductionmentioning
confidence: 99%